Success Rate of Endoscopic Third Ventriculostomy in Children Younger Than 1 Year With Idiopathic Congenital Aqueductal Stenosis and Long-term Follow-up - Krejcí, Tomáš; Kubina, Lukáš; Krejcí, Ondrej; Chlachula, Martin; Lipina, Radim (Journal of child neurology, 2025)
INTRODUCTION: The indication for endoscopic third ventriculostomy is often contested in children younger than 1 year. This study aims to establish the benefits of this modality in children with idiopathic congenital aqueductal stenosis. METHODS: Retrospective analysis was performed on patients <1 year old with idiopathic congenital aqueductal stenosis undergoing endoscopic third ventriculostomy between 2004 and 2020. Preoperative cerebral imaging was performed in all cases. Endoscopic third ventriculostomy efficacy and overall patient outcome were evaluated over the entirety of the monitoring period averaging 146 months (range, 34-218 months). Outcome was assessed by modified Rankin Scale score. Treatment success was assessed in relation to the Endoscopic Third Ventriculostomy Success Score (ETVSS), patient age, and perioperative findings of membranes in the interpeduncular cistern. RESULTS: The study comprised 14 children aged from 6 to 280 days, mean age 16 weeks, with 11 patients aged <6 months. The characteristic presentation was progressive macrocephaly, with the setting sun sign in 2 cases. The overall Endoscopic Third Ventriculostomy Success Score was 52.1%, whereas endoscopic third ventriculostomy was successful in 12 patients (85.7%) in the first year postoperation and in 11 cases (78.6%) in the long term. Endoscopic third ventriculostomy failure was not related to patient age (P > .99) or perioperative findings of interpeduncular cistern membranes (P = .51). Patient outcome averaged modified Rankin Scale score 1. Most children were without or with minimal disability. CONCLUSIONS: We consider endoscopic third ventriculostomy a safe and effective modality for the initial treatment of patients aged <1 year presenting with congenital aqueductal stenosis-based hydrocephalus.
Keywords: třetí mozková komora; Hydrocephalus; Retrospective Studies; kojenec; výsledek terapie; mužské pohlaví; Infant; Follow-Up Studies; následné studie; Infant, Newborn; Child, Preschool; ženské pohlaví; novorozenec; aqueduct stenosis; neuroendoskopie; retrospektivní studie; předškolní dítě; Humans; hydrocephalus; hydrocefalus; infant; Neuroendoscopy; ventrikulostomie; endoscopic third ventriculostomy; Female; Ventriculostomy; Treatment Outcome; Third Ventricle; lidé; Male